Translation as secondary communication. The relevance theory perspective of Ernst-August Gutt - K. Smith (Acta Theologica)
Ernst-August Gutt started one of the greatest translation debates of the past ten years when he suggested that relevance theory holds the key to providing a unified account of translation. The bulk of the debate has been between practitioners of functional equivalence and advocates of a relevance theoretic approach to translation. However, opponents of the relevance theoretic approach have widely misunderstood Gutt’s claims and objectives, with the result that too much discussion has focused on minor points of his account of translation. This article will attempt to clarify his objectives and claims, and to clear up some common misunderstandings about the implications of embracing a relevance theoretic approach to translation.